Gender Equitable Physical Education: A Phenomenological Study in an Islamic Elementary School Teacher Education Program - Hasan; Ranti, Gemala; Mahyuddin (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
Gender equality in physical education remains a critical issue, particularly in the Department of Islamic Elementary School Teacher Education (PGMI) at the State Institute of Islamic Studies of Bone, where social constructs and gender stereotypes often hinder female students’ active participation in physical activities. This study aims to explore the experiences, views, and perceptions of students and lecturers regarding gender equality practices in physical education, and how inclusive learning spaces can dismantle symbolic domination and foster social transformation. This qualitative study employed a phenomenological design, involving 10 female students and two lecturers as key participants. Data was collected through in-depth interviews, participatory observations, and curriculum document analysis. The findings indicate that female students demonstrated increased self-confidence, active engagement, and a shift in perceptions toward sports after participating in inclusive, gender responsive learning. The learning environment also promoted collaborative interactions between male and female students, supported by the strategic role of lecturers as facilitators of justice-based values. In the context of Islamic higher education institutions, this approach successfully integrates religious values with gender equality principles in a harmonious way. The study concludes that physical education plays a strategic role as a medium for social transformation, not only enhancing physical fitness but also fostering critical awareness of equity and social justice. This study implies that gender-equitable physical education training in PGMI contributes to shaping inclusive future teachers who promote equal participation in primary classrooms.